(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This scientific article provides a comprehensive study of the role of the service sector and the tourism industry within the national economy, their mutual integration, and their impact on regional socio-economic development. The research analyzes the theoretical, methodological, and practical aspects of how the development of services and tourism influences economic growth, employment rates, investment flows, and regional economic security. Furthermore, the study explores the institutional mechanisms for developing the service and tourism sectors and formulates scientifically grounded proposals and recommendations for their enhancement.